Opening Remarks at Press Conference in Beijing, China, July 17, 2015 - Kim, Jim Yong (2016)
These remarks delivered by Jim Yong Kim, President of the World Bank Group, discuss the Chinese economy, China's global role in development, and the latest report on health care reform. He appreciated China, that remains the largest contributor to world growth since the global financial crisis. He talks about the progress made by China in several reforms, including lower credit growth, better regulation of shadow banking, and better management of local government borrowing and these reforms hold the key to its continued economic success. He addresses huge infrastructure needs that are critical to end poverty, reducing inequality, and boosting shared prosperity in the world and China's committment to support financially for the same. He concludes by talking about more efficient health care system in China that will lead to a healthier population, boost economic growth and become an engine for job creation.